Pharmacogenomics - Ingelman-Sundberg, Magnus (Henry Stewart Talks, 2007)
Pharmacogenomics and adverse drug reactions, Evolutionary basis of pharmacogenomics and interethnic differences, Deletion, duplication, multiduplication or amplification of active P450 genes, Importance of polymorphism of drug metabolizing genes and drug targets for drug therapy, The importance of rare mutations for precision medicine, Drug pharmacogenomics labels and their clinical use
Updated at 2016/08/31, Archived at 2023/06/29